2006
DOI: 10.1007/s10495-006-6795-2
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Fas-induced apoptosis by inhibition of extracellular phosphorylation of Fas receptor in Jurkat cell line

Abstract: Apoptosis signalling through the Fas pathway requires several steps of aggregation of the Fas receptor in the membrane, including aggregation that may occur in the absence of Fas ligand. Association of Fas domains is determinant to signal transmission following Fas ligand binding to a specific domain. The domains involved in Fas aggregation are located in its extracellular region and contain three potential protein kinase C-binding motifs. We therefore studied the possibility that phosphorylation of the extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…Extracellular protein phosphorylation/dephosphorylation is known to affect many aspects of cellular signaling [53,54], and is involved in platelet aggregation [55-57]. The conserved basic nature of all flea salivary phosphatases points to interaction with a negatively charged target.…”
Section: Resultsmentioning
confidence: 99%
“…Extracellular protein phosphorylation/dephosphorylation is known to affect many aspects of cellular signaling [53,54], and is involved in platelet aggregation [55-57]. The conserved basic nature of all flea salivary phosphatases points to interaction with a negatively charged target.…”
Section: Resultsmentioning
confidence: 99%
“…Our results support the observations of Zhou et al [13] who found that among nine tested Bis derivatives ultimately Bis-VIII and Bis-IX promoted Fas-induced apoptosis rather then Bis-I, Bis-II, Bis-III, Bis-IV, Bis-V, Bis-X and Bis-XI. It is worth to note, that Bisindolylmaleimides were initially described as PKC inhibitors [10,11,28]. In particular, Bis-III is believed to block PKCdependent activation of c-Raf-1, the known downstream target of PKC [18].…”
Section: Discussionmentioning
confidence: 99%
“…Based on molecular modeling it is proposed that feG exerts its antiinflammatory actions by binding to the hydrophobic pocket in the kinase domain that is normally occupied by the hydrophobic motif [82,83]. PKC has a predominant intracellular location, but certain inflammation conditions induce its movement to the extracellular surface where it has possible roles in apoptosis [84,85] and cell adhesion [86,87].…”
Section: A Human Homologue Of Sialorphin -Opiorphinmentioning
confidence: 99%
“…feG significantly inhibits the binding of peritoneal leukocytes to fibrinogen and fibronectin, and may exert these anti-adhesive actions by interfering with cell adhesion molecules in that: -binding of CD11b (αM integrin) and CD16b (FcγRIIIb: low-affi nity IgG receptor IIIB) of human neutrophils and rat leukocytes [95] is reduced; -expression of CD49d (α4 integrin) on peritoneal neutrophils and circulating leukocytes collected from ovalbumin sensitized rats 24 h aft er challenge [106] is downregulated; modulating PKC activity [82,83]. PKC has been demonstrated to be externalized in several models of infl ammation [84,87], a position where it would be amendable to interaction with SGP-T and homologues for modulation of enzymatic activity and infl ammatory processes.…”
Section: Cellular Mechanism Of Action Of Sgp-t and Fegmentioning
confidence: 99%